Ideological perspective on guideline “merdeka belajar – kampus merdeka” through systemic functional linguistics - Prayudisti Shinta Pandanwangi; Pratomo Widodo (Faculty of Languages, Arts, and Culture Universitas Negeri Yogyakarta, 2022)
This research exists to ignite the awareness and critical thinking from stakeholders and parties related to MBKM policies that have a long ideological impact on the life of higher education in Indonesia so that the implementers do not necessarily carry out policies without conducting assessments in depth first. Therefore, this study aims to explore and find the ideological and socio-political aspects behind the use of the lexicon in the Merdeka Learning guidebook – Merdeka Campus (MBKM) using textual metafunction and interpersonal metafunction approach model within Halliday's SFL framework (2004 2013). These textual and interpersonal approaches were chosen due to the scarcity of studies that apply this approach to analyze the discourse of this independent curriculum compared to studies of other disciplines. The data used in this study are in the form of lexicons used in the MBKM manual book as words or clauses within the chosen chapters. The result obtained is that the MBKM practical guidebook has a strong capitalist economic perspective. This is evidenced using lexicons that indicate the direction of higher education to be achieved tends to follow the circulation of the free market and higher education and all stakeholders involved are regulated to follow this globalization trend. “Independent Campus – Merdeka Learning” requires students to be able to equip themselves to survive life's challenges. In contrast, the campus as an “intellectual factory” is always billed for the needs of the industrial sector, not a place for “true intellectuals”.Keywords: SFL, CDA, independent learning – independent campus, capitalization of higher education Perspektif ideologis tentang pedoman